Efficacy of information and communication technology in digitalized students’ records management in universities in Eastern Uganda - Ochwo, Deogracious; Zami Atibuni, Dennis; Sekiwu, Denis (African Educational Research Journal, 2018)
This quantitative study examined the efficacy of adopting information and communication technology (ICT) in digitalized students’ records management among university staffs in Eastern Uganda. The study used cross-sectional and descriptive survey designs. The target population was 402 staff members involved in students’ records management, of which 129 participants were obtained using stratified, proportionate, and simple random sampling techniques. Data were collected using a self-administered questionnaire that measured the levels of ICT adoption and effectiveness of digitalized students’ records management. Findings revealed that the level of ICT adoption and digitalised students’ records management in the universities was generally moderately high. It was further revealed that an increase in the level of ICT adoption was associated with higher effectiveness of digitalized students’ records management and vice versa. It was recommended that managements of the universities need to procure enough ICT equipment such as computers for the staff to promote effective digitalized students’ records management. Training needs assessment and continuous professional training in the field of ICT was required all the time for the staff to keep abreast technological changes in students’ records management.
Keywords: ICT adoption; Records management; Digital; University